Design, synthesis and biological evaluation of alkylamino biphenylamides as Hsp90 C-terminal inhibitors. Issue 2 (15th January 2017) - Garg, Gaurav; Zhao, Huiping; Blagg, Brian S.J.
Graphical abstract: Abstract: Hsp90 is a promising therapeutic target for the development of anti-cancer agents due to its integral role in the stability and function of proteins associated with all ten hallmarks of cancer. Novobiocin, a coumarin antibiotic, was the first natural product identified that targeted the Hsp90 C-terminal domain and manifested anti-proliferative activity (SKBr3 IC50 ∼ 700 μM). Subsequent structural investigations on novobiocin led to analogues with significantly improved anti-proliferative activity against multiple cancer cell lines. In an effort to develop more efficacious and diverse analogues, it was recently found that the coumarin ring of novobiocin could be replaced with the biphenyl core without compromising activity. Based on these prior studies, a series of alkylamino biphenylamides was designed, synthesized and evaluated for anti-proliferative activity against two breast cancer cell lines. SAR studies demonstrated that the incorporation of an alkylamino side chain onto the biphenyl core improved anti-proliferative activity and resulted in compounds that exhibit sub-micromolar to mid-nanomolar activity through Hsp90 inhibition. Importantly, these studies indicate the presence of a hydrophilic region about the central core that can be exploited for the design of new inhibitors.